Towards host-directed therapies for tuberculosis. - Zumla,A; Maeurer,M; Host-Directed,Therapies Network; Chakaya,J; Hoelscher,M; Ntoumi,F; Rustomjee,R; Vilaplana,C; Yeboah-Manu,D; Rasolof,V; Munderi,P; Singh,N; et al. (Nature reviews. Drug discovery, 2015)
The treatment of tuberculosis is based on combinations of drugs that directly target Mycobacterium tuberculosis. A new global initiative is now focusing on a complementary approach of developing adjunct host-directed therapies.